Оптимізація процесу плазмового осадження покриттів Cu–Al2O3 з покращеними тепло- та електроізоляційними властивостями - Бова, Дмитро Костянтинович (Харківський національний автомобільно-дорожній університет, 2025)
The task of the qualification work is to develop a special thermal and electrical insulating coating based on Cu+Al2O3 , which is used for internal heating inductors. Inductors operate at high temperatures, so the material must have high thermal resistance and electrical insulation resistance. During the qualification work, methods for obtaining gas-thermal coatings were considered. Among all the methods considered, plasma spraying is promising and therefore was used to form the coating. The analysis of materials conducted in the literature review allowed us to select a composite material based on Cu+Al2O3 , which became the sublayer for forming a thermal and electrical insulating coating to protect inductors. Using the developed technology, a thermal and electrical insulating coating was applied to the outer surface of the inductor, which is used for internal heating. Such a coating, obtained by plasma spraying, is an effective means of protecting the inductor from electrical breakdown.
Optimization of the plasma deposition process of CU–AL₂ O₃ coatings with enhanced thermal and electrical insulating properties
Keywords: plasma; spraying; coating; inductor; research; wear resistance; plasma-generating; products; gas thermal